Bioelectrode based chitosan-nano copper oxide for application to lipase biosensor - Bodade, A B; Taiwade, M A; Chaudhari, G N (Creative Pharma Assent, 2017)
Chitosan (Chit)-nanocrystalline CuO composite prepared from Chitosan and CuO nanoparticles by a spin coating method. CuO nanoparticles (45 nm) synthesized by Sol-gel citrate method and characterized by X-Ray diffraction (XRD), Raman spectroscopy, UV-visible spectroscopy, Fourier transform spectroscopy (FTIR) and Scanning electron microscopy (SEM). The electrochemical studies revels that these Chit-nano CuO electrode provide favorable condition for immobilization of enzyme lipase [LIP] specific enzyme for triglyceride detection, resulting in enhanced electron transfer at the interface. The prepared bioelctrode (LIP/Chit-nano CuO/Au bioelectrode) is utilized for triglyceride [TG] sensing using cyclic voltammetry (CV) with hexacyanoferrate as mediator. The electrochemical response studies shows on improved sensing performance of bioelectrode exhibit high sensitivity, low detection limit and good linearity of tributyrin concentration with fast response time. The low value of Michallis-Menten constant indicates high affinity of LIP towards the analyte (tributyrin). The Redox behavior of nano CuO makes an efficient matrix with chitosan for triglyceride [TG] biosensor.